2020
DOI: 10.1038/s41418-019-0488-1
|View full text |Cite
|
Sign up to set email alerts
|

AXL and CAV-1 play a role for MTH1 inhibitor TH1579 sensitivity in cutaneous malignant melanoma

Abstract: Cutaneous malignant melanoma (CMM) is the deadliest form of skin cancer and clinically challenging due to its propensity to develop therapy resistance. Reactive oxygen species (ROS) can induce DNA damage and play a significant role in CMM. MTH1 protein protects from ROS damage and is often overexpressed in different cancer types including CMM. Herein, we report that MTH1 inhibitor TH1579 induced ROS levels, increased DNA damage responses, caused mitotic arrest and suppressed CMM proliferation leading to cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…We next investigated the effect of tagitinin C on colony formation in HCT116 cells by clonogenic cell survival assay 28 - 30 . As shown in Figure 2 A-B, tagitinin C induced a significant concentration-dependent reduction in the number of colonies after 14 days treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the effect of tagitinin C on colony formation in HCT116 cells by clonogenic cell survival assay 28 - 30 . As shown in Figure 2 A-B, tagitinin C induced a significant concentration-dependent reduction in the number of colonies after 14 days treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It is often overexpressed in various types of cancer including CMM (Wang et al, 2018). We recently reported that combining the MTH1 inhibitor TH1579 with a BRAF J o u r n a l P r e -p r o o f inhibitor further augments cell death in BRAFV600 mutant CMM cells compared to either inhibitor alone (Das et al, 2020).…”
Section: To the Editormentioning
confidence: 99%
“…Zebrafish xenografts assays have been frequently incorporated into studies on the control of cancer growth, invasion, and migration. Components of cancer-related pathways have been altered by gene mutations [34,35], gene overexpression or knockdown [35][36][37][38][39][40][41][42], protein inactivation by antibody binding [41], pharmacological inhibition of protein function [34,36,42,43], and cell culture selection for drug resistance [32,43]. In many of these studies, zebrafish xenograft models were run in parallel with mouse models, which reported comparable results [34,[36][37][38][41][42][43].…”
Section: Zebrafish Xenografts Clarify the Mechanistic Underpinnings Of Tumor Cell Behaviors And Their Interactions With The Cancer-associmentioning
confidence: 99%
“…In addition, zebrafish xenografts have enabled the study of several novel therapies, including ectopic overexpression of protein deacetylases, epigenetic modulators, VEGFR inhibitors, and inhibition of SMYD3, CDCA7, MTH1, and p38b/CK2/SET [34,42,[57][58][59].…”
Section: Zebrafish Xenografts Facilitate the Identification Of New Drug Targets For Metastatic Cancersmentioning
confidence: 99%